Precision of jaw-closing movements for different jaw gaps - Hellmann, Daniel; Becker, Georg; Giannakopoulos, Nikolaos Nikitas; Eberhard, Lydia; Fingerhut, Christopher; Rammelsberg, Peter; Schindler, Hans J. (European journal of oral sciences, 2014)
Jaw-closing movements are basic components of physiological motor actions precisely achieving intercuspation without significant interference. The main purpose of this study was to test the hypothesis that, despite an imperfect intercuspal position, the precision of jaw-closing movements fluctuates within the range of physiological closing movements indispensable for meeting intercuspation without significant interference. For 35 healthy subjects, condylar and incisal point positions for fast and slow jaw-closing, interrupted at different jaw gaps by the use of frontal occlusal plateaus, were compared with uninterrupted physiological jaw closing, with identical jaw gaps, using a telemetric system for measuring jaw position. Examiner-guided centric relation served as a clinically relevant reference position. For jaw gaps ≤4 mm, no significant horizontal or vertical displacement differences were observed for the incisal or condylar points among physiological, fast, and slow jaw-closing. However, the jaw positions under these three closing conditions differed significantly from guided centric relation for nearly all experimental jaw gaps. The findings provide evidence of stringent neuromuscular control of jaw-closing movements in the vicinity of intercuspation. These results might be of clinical relevance to occlusal intervention with different objectives.